Synthesis and Evaluation of Novel DNA Minor Groove Binders as Antiamoebic Agents - Hasan Y. Alniss; Naveed A. Khan; Anania Boghossian; Noor Akbar; Hadeel M. Al-Jubeh; Yousef A. Msallam; Balsam Q. Saeed; Ruqaiyyah Siddiqui (Antibiotics, 2022)
The free-living amoeba Acanthamoeba castellanii is responsible for the central nervous infection granulomatous amoebic encephalitis and sight-threatening infection Acanthamoeba keratitis. Moreover, no effective treatment is currently present, and a combination drug therapy is used. In this study, twelve DNA minor groove binders (MGBs) were synthesized and tested for their antiamoebic activity via amoebicidal, encystation, excystation, and cytopathogenicity assays. It was found that the compounds MGB3, MGB6, MGB22, MGB24, and MGB16 significantly reduce amoeba viability to 76.20%, 59.45%, 66.5%, 39.32%, and 43.21%, respectively, in amoebicidal assays. Moreover, the compounds MGB6, MGB20, MGB22, MGB28, MGB30, MGB32, and MGB16 significantly inhibit Acanthamoeba cysts, leading to the development of only 46.3%, 39%, 30.3%, 29.6%, 27.8%, 41.5%, and 45.6% cysts. Additionally, the compounds MGB3, MGB4, MGB6, MGB22, MGB24, MGB28, MGB32, and MGB16 significantly reduce the re-emergence of cysts to trophozoites, with viable trophozoites being only 64.3%, 47.3%, 41.4%, 52.9%, 55.4%, 40.6%, 62.1%, and 51.7%. Moreover, the compounds MGB3, MGB4, and MGB6 exhibited the greatest reduction in amoeba-mediated host-cell death, with cell death reduced to 41.5%, 49.4%, and 49.5%. With the following determined, future in vivo studies can be carried out to understand the effect of the compounds on animal models such as mice.